Periodic lateralized epileptiform discharges in neuropsychiatric lupus: Association with cerebritis in magnetic resonance imaging and resolution after intravenous immunoglobulin - Lim, K-S; Cheong, K-L; Tan, C-T (Arnold Publishers (journals now owned by Sage), 2010)
A 13-year-old girl with a known diagnosis of systemic lupus erythematosus presented with seizures and psychosis. An electroencephalogram (EEG) revealed continuous, non-evolving periodic lateralized epileptiform discharges (PLEDs) in the left temporal region, which did not resolve with benzodiazepine. A magnetic resonance imaging (MRI) brain scan demonstrated a focal hyperintensity in the left medial temporal and left occipital lobes, left thalamus and bilateral cerebellar white matter, with evidence of vasculitis in the magnetic resonance angiography. Intravenous immunoglobulin was given because of failed steroid therapy, which resulted in a full resolution of clinical, EEG and MRI abnormalities. Lupus cerebritis should be considered as a possible aetiology in PLEDs, and immunoglobulin can be effective in neuropsychiatric lupus. Lupus (2010) 19, 748-752.